Farmer Awareness and Socio Economic Determinants of PM KUSUM Adoption in Uttar Pradesh, India - , Kaushlendra Srivastava; Supriya,; , Km. Deepshikha; , Soumya Ranjan Mohapatra; , Sooraj Kumar; , Akanksha Chaturvedi; , Abhishek Verma (Archives of Current Research International, 2025)
Solar irrigation pumps are a major advancement in agricultural technology, offering farmers a sustainable solution to irrigation while reducing dependence on conventional energy sources. In India, small and marginal farmers often face financial and climatic challenges, limiting the adoption of such innovations. Despite government support through the PM-KUSUM Scheme (Component B), uptake remains modest due to financial constraints and low awareness. This study examines the socio-economic factors influencing the awareness and adoption of solar pumps. Illiteracy, influenced by factors such as gender, age, caste, and family structure, remains widespread, especially among females, lower castes, and joint families. Primary data were collected through a structured schedule with selected farmers. Analytical tools such as averages, percentages, and means were used to analyze socio-economic factors, while Binary Logistic Regression analysis was performed using SPSS to identify the major factors influencing adoption. Income levels of both illiterate and graduate farmers were similar, suggesting that income is tied more to access to resources than education. Awareness of the scheme was spread mainly through friends and relatives (30.95%), agricultural officers (27.38%), and social media (22.62%). While many farmers understood the procedures, technical knowledge, especially regarding solar panel maintenance, was lacking. Binary logistic regression showed occupation, landholding size, caste, and education as key adoption factors. The study emphasizes the need for targeted outreach to smallholders through mass media, fairs, meetings, and demonstrations.